Journal of Activity, Sedentary and Sleep Behaviors - Vandelanotte, Corneel; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
JASSB focuses on the areas of physical activity, sedentary behavior, and sleep research. The journal embraces the development of knowledge and research that adopts a 24-hour approach when examining or manipulating physical activity, sedentary and sleep behaviors and their effect on health. Submissions that examine at least two of these behaviors simultaneously are encouraged. Behavioral interventions, randomised controlled trials, epidemiological studies, cross-sectional surveys, systematic reviews and compositional data analysis are all welcomed, as well as studies focussing on assessment technology or interventions with a focus on digital health.
Keywords: Public health; Public Health